Tourism English Training for The Students of Ensino Secundario Sao Pedro, Dili, Timor Leste - I Nyoman Muliana; I Nyoman Kardana; I Gusti Ayu Agung Dian Susanthi; Charles Fatima Guterres; Jorge de Orleans (Postgraduated Community Service Journal, 2025)
This community service program was done by a collaboration team between Linguistics Master Program, Postgraduate Faculty, Warmadewa University, Denpasar and English Department, Faculty Science of Education, Instituto Superior Cristal, Dili. Before it was conducted, both parties had made discussions and decided that the program took place at Ensino Secundario Sao Pedro, a senior high school in Dili, Timor Leste with the headmaster as partner and 20 students as target audience. The theme of the program selected was tourism English training with the aim to enhance the students’ proficiency in tourism English so that in the future they would be able to compete in tourism sector especially in Dili and in Timor Leste in general. The observation activities of the team before the performance of the program had showed that Timor Leste has many tourism potencies of nature, beaches, and historical remains supported by friendliness of the people. The method applied was audio-lingual method focusing on listening and speaking. The result of the final test of the program shows that 17 participants (85%) reached very good scores and 3 participants (15%) had good scores in three aspects of tourism English, namely vocabularies and English functions.